Pengaruh Pemahaman Aspek Keselamatan Terhadap Tidak Merokok dan Implikasinya Bagi Peraturan Pemerintah Berkaitan dengan Rokok - Wiwit Didik Setiaji; Ratna Katharina; Aeron Frior Sihombing (Sekolah Tinggi Teologi SAPPI Ciranjang, 2016)
Smoking cigarette has been practicing by people for a long time ago and it already become one of people lifestyles. Currently, smoking cigarette has been a big issue in the world. Many publications have reported the negative impacts of the cigarette to the human health, social and nature enviroments. As a result, many countries, including Indonesia, have made regulations due to cigarette impacts, such as not smoking in the public areas and also no cigarette advertisement in social media and public areas. Governments have given informations to people the reason why they need to stop smoking. Nevertheless, still many people keep smoking even disobey the relugations, likewise many Christians. This study aims to know the response of many Christians due to those regulations. The study proved that respondents have a well understanding of salvation aspects and it influences them in decision not to smoke cigarette.